Tracking circulating tumour‐associated T cells for the early diagnosis of cancer. Issue 2 (20th June 2022) - Notarbartolo, Samuele
Abstract : Cancer patients have greater chances of being cured if diagnosed at early stages. Integrated information on TCR repertoire and transcriptional signatures of circulating tumour‐associated T cells promise the future development of antigen‐agnostic minimally invasive tests able to diagnose early‐stage cancer.